THE PREVENTIVE PRISON AND INTERNATIONAL LAW - Peruana de Derecho Internacional, Sociedad (2020)
The article focuses on the phenomenon of pre-trial detention abuse in the Latin AmericanRegion, mainly in light of the American Convention on Human Rights and the UN Pact onthe same subject, analyzing the legal currents on its application and its consequences in thePeruvian legislation, concluding in the formulation of recommendations.